2020
DOI: 10.7717/peerj.10365
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trend of cardiorespiratory endurance in urban Catalan high school students over a 20 year period

Abstract: Background Physical fitness is considered an important indicator of health in adolescents. However, in recent years several studies in the scientific literature have shown a considerable lower trend and an alarming worsening of the current adolescents’ physical condition when comparing with previous decades, especially in urban populations. The aim of the current study was to analyse the temporal trend in cardiorespiratory endurance (CRE) in urban Catalan adolescents over a 20-year period (1999–2019). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The decrease in the level of daily physical activity and the adoption of sedentary behaviors are related to lower adherence to the Mediterranean diet (AMD) [ 7 ], lower performance on physical fitness tests [ 8 ], and higher percentage of fat mass [ 9 ]. This forms a serious problem for the health of the adolescent population because in recent years there has been a decline in physical capacities, mainly affecting strength [ 10 ] and cardiorespiratory capacity [ 11 , 12 ], as well as an increased number of diseases related to poor nutrition [ 13 ] and accumulation of fat mass [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The decrease in the level of daily physical activity and the adoption of sedentary behaviors are related to lower adherence to the Mediterranean diet (AMD) [ 7 ], lower performance on physical fitness tests [ 8 ], and higher percentage of fat mass [ 9 ]. This forms a serious problem for the health of the adolescent population because in recent years there has been a decline in physical capacities, mainly affecting strength [ 10 ] and cardiorespiratory capacity [ 11 , 12 ], as well as an increased number of diseases related to poor nutrition [ 13 ] and accumulation of fat mass [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obesity in childhood were identified as health problems in several studies [ 15 , 26 , 44 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to research on the assessment of the applied fitness tests, the study conducted by Armstrong and Welsman (2007) [25] confirmed a negative impact of BMI increase on aerobic fitness achievement. Arboix-Alió et al (2020) [26] also highlight an alarming deterioration in the physical fitness of adolescents compared to previous decades, especially among urban populations, with respect to the evolution of cardiorespiratory fitness (CRF) over time, analyzing 20 years. Tomkinson et al's (2019) research, covering 33 years showed, a modest reduction in CRF [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inactivity is considered a risk factor related to some diseases such as obesity and diabetes [2,3]. Indeed, in recent years, several investigations have revealed a considerable decrease in the physical fitness levels of adolescents and children [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%